Adolescent addiction epidemiology, assessment and treatment (Practical resources for the mental health professional, 2008)
Adolescent Addiction: Epidemiology, Assessment, and Treatment presents a comprehensive review of information on adolescent addiction, including prevalence and co-morbidity rates, risk factors to addiction, and prevention and treatment strategies. Unlike other books that may focus on one specific addiction, this book covers a wide range of addictions in adolescents, including alcohol, cannabis, tobacco, eating, gambling, internet and video games, and sex addiction. Intended to be of practical use to clinicians treating adolescent addiction, the book contains a wealth of information that will be of use to the researcher as well. A global perspective is offer from international contributors, representing the US, Canada, the UK, New Zealand, and Australia. * Comprehensive with the state-of-the-art information on important and the most common adolescent addiction * Easy to understand and organized chapters * Written by international experts